Interactive object-oriented programming in Java : learn and test your programming skills - Sarcar, Vaskaran (Apress, 2020)
Gain the fundamental concepts of object-oriented programming with examples in Java. This second edition comes with detailed coverage and enhanced discussion on fundamental topics such as inheritance, polymorphism, abstract classes, interfaces, and packages. This edition also includes discussions on multithread programming, generic programming, database programming, and exception handling mechanisms in Java. Finally, you will get a quick overview of design patterns including the full implementation of some important patterns. Interactive Object-Oriented Programming in Java begins with the fundamental concepts of object-oriented programming alongside Q & A sessions to further explore the topic. The book concludes with FAQs from all chapters. It also contains a section to test your skills in the language basics with examples to understand Java fundamentals including loops, arrays, and strings. Youll use the Eclipse IDE to demonstrate the code examples in the book. After reading the book, you will have enhanced your skills in object-oriented programming in Java and you will be able to extend them in interesting ways. You will: Discover object-oriented programming with Java Test your programming skills Crack Java-based interviews with confidence Use the Eclipse IDE to write code and generate output.